Aging, inflammation and the environment - Bektas, Arsun; Schurman, Shepherd H.; Sen, Ranjan; Ferrucci, Luigi (Experimental gerontology, 2018)
The aging process is driven by interrelated mechanisms that lead to the emergence of characteristic phenotypes that include changes in body composition, energy production and utilization imbalance, homeostatic dysregulation, and neurodegeneration and loss of neuroplasticity. Mainstream theories of aging all recognize that the aging phenotypes result from an imbalance between stressors and stress buffering mechanisms and a resultant loss of compensatory reserve leading to accumulation of unrepaired damage. This in turn results in increased disease susceptibility, reduced functional reserve, reduced healing capacity and stress resistance, unstable health and finally failure to thrive. The resultant physical and cognitive decline that culminates with the frailty syndrome is a tipping point of healthspan and implies a high risk of system decompensation and death. Preserving physical and cognitive function is the main focus of geriatric and gerontological research, but it is important to recognize that accomplishing this goal requires a profound understanding of the molecular, cellular and physiological mechanisms that ultimately determine functional changes. In this context, the proinflammatory state of aging plays a major role. Longitudinal studies have shown that with aging most individuals tend to develop a chronic low-grade proinflammatory state, and that such a state is a strong risk factor for multimorbidity, physical and cognitive disability, frailty and death. A number of environmental factors may play an important role in modifying the proinflammatory state. We explore processes and mechanisms of aging that affect human biology and the possible links of inflammation and the environment to aging, especially those related to metabolism. We point out that longitudinal studies with a life course approach are needed to gain further mechanistic insight on the processes that lead to functional decline with aging, and the role played in this process by inflammation and environmental challenges. •Aging causes changes in body composition, energy imbalance, homeostatic dysregulation, and neurodegeneration.•These systemic changes lead to increased disease susceptibility, unstable health, and finally physical and cognitive frailty.•Chronic inflammation, inflamm-aging, may be the common mechanism predisposing individuals to chronic age-related diseases.•Many mechanisms of aging interact with environmental factors especially in the context of metabolism.•Longitudinal studies are important to link lifetime exposures, biological changes, and functional consequences of aging.